Kristy's big news - Martin, Ann M., 1955- (New York : Scholastic, 1999)
Kristy and her brothers haven't seen their divorced father for years, when they receive the surprising news that he's getting married and wants them to travel to California for the wedding.
"An Apple paperback."
RL 4.
008-012.
690
Keywords: Divorced fathers -- Fiction; Remarriage -- Fiction; Father and child -- Fiction